Design and Development of a Coconut Milk pH Monitoring System via WhatsApp Notifications at PT. Sasa Inti Minahasa Selatan - Sitti Wetenriajeng Sidehabi; Al Mahdali; Fadlan Tri Antono (UPPM Poltek ATI Makassar, 2025)
The quality of coconut milk is a crucial aspect in the production process at PT Sasa Inti Minahasa Selatan. Manual quality assessments of coconut milk often consume time and may lead to inaccuracies. To address this issue, this study aims to design and develop a pH monitoring system for coconut milk that can automatically send notifications via WhatsApp. The system uses a pH sensor connected to a microcontroller to monitor the pH level of the coconut milk in real-time. The pH data obtained is processed by the microcontroller and sent via API to the WhatsApp application when the pH level falls outside the predefined range. Test results indicate that the system can accurately measure pH levels and send timely notifications, allowing operators to take corrective actions quickly. The implementation of this monitoring system is expected to improve the efficiency of coconut milk quality monitoring and reduce the risk of defective products, thereby positively contributing to the overall production quality at PT Sasa Inti Minahasa Selatan.